Leaching and residual activity of imidazolinone herbicides in lowland soils - Refatti,João Paulo (2017)
ABSTRACT: Herbicides used in the Clearfield® rice (Oryza sativa L.) production system have a potential for leaching. This can result in contamination of underground water resources and cause injury to not tolerant crops that are sown in a succession and/or crop rotation. The objective of this study was to determine the leaching potential and the residual activity of the herbicides used in the Clearfield® rice system. The experiment was conducted over a period of two years and consisted of conducting a field test to be followed by two bioassays with a year of difference between their implementation. Initially an experiment was conducted in lowland area where it was planted the cultivar of rice ‘PUITA INTA CL’. Approximately one and two years thereafter, soil samples from each plot were collected at intervals of 5cm to a depth of 30cm (B factor) for the bioassay to evaluate persistence of herbicides. Factor A was composed of mixtures formulated of imazethapyr + imazapic (75 + 25g a.i. L-1), imazapyr + imazapic (525 + 175g a.i. kg-1) in two doses, imazethapyr (100g a.i. L-1) and treatment control without application. Basing on results, it was concluded that the mixtures imazethapyr + imazapic, imazapyr + imazapic and imazethapyr leached into the soil, reaching depths of up to 25cm in lowland soil. Imidazolinone herbicides used today in the irrigated rice Clearfield® system are persistent in soil, and their phytotoxic activity can be observed up to two years after application.